Assessment of Intellectual Development of the Human Capital of Hi-Tech Productions - Evgeny Popov; Maxim Vlasov (Montenegrin Journal of Economics)
The subject of research are the directions of development of the intellectual capital at the hi-tech enterprises. Objective of this research is development of almost applicable technique of quantitative assessment of the generation of knowledge for the hi-tech enterprises allowing to make evidence-based administrative decisions. Research hypothesis. Authors consider that at the hi-tech enterprises the chelovesky capital is a basis of development of the intellectual capital. The author proposes the following definition: the human capital of high-tech enterprises consists in a set of abilities and skills obtained because of training, as well as the scientific activities of workers necessary for the effective operation of the enterprise. Within the framework of this study, the hu-man capital of the firm will be considered only from the point of view of intellectual activity. In connection with the basis for increasing the competitiveness of products in high-tech enterprises being to increase the efficiency of intellectual activity, which is primarily ensured by the continuous improvement of the qualifications of scientific workers. Authors have received the indicator "an intellectual share in development of the human capital" which is quantitative assessment of generation of knowledge of the hi-tech enterprises. An indicator "the intellectual share in development of the human capital" represents the relation of a gain of the intellectual capital to a gain of the human capital. On each of stages life cycle of a product, it is necessary to count separately an indicator "an intellectual share in development of the human capital" because on each of stages intellectual and human the capital of the hi-tech enterprise have different components. The theoretical importance consists in receiving an indicator "an intellectual share in development of the human capital" developing the methodical device of economy of knowledge which can become further a basis for quantitative assessment of processes of generation in various fields of managing.